Contemporary Cultural Da'wah: The Relevance of Art as a Medium of Religious Transformation in Pagutan Karang Genteng - Samsudin, Ahmad; Suprapto, Suprapto (AS-SABIQUN, 2026)
This study is motivated by the limited research on how diverse artistic expressions collectively function as media of religious transformation, despite their significant impact on contemporary cultural da’wah practices in local Muslim communities. It aims to explore how cultural art forms are utilized in da’wah, analyze their relevance and effectiveness in shaping religious transformation, and identify the supporting and inhibiting factors influencing art-based da’wah in Pagutan Karang Genteng. A qualitative intrinsic case-study design was employed, involving 18 purposively selected participants representing religious leaders, local artists, community figures, and audience members. Data were collected through semi-structured interviews, participant observation of artistic–religious events, and document analysis, and were examined using reflexive thematic analysis. The findings reveal that diverse artistic expressions—vocal, performative, and visual—are deeply embedded in community religious life and serve as effective tools for transmitting Islamic teachings. Art-based da’wah is actively practiced and integrated into religious gatherings, youth activities, and communal events, fostering emotional engagement, increasing public participation, and contributing to observable improvements in religious attitudes and behavior. Supporting factors include strong collaboration among religious leaders and artists, cultural continuity, and youth involvement, whereas inhibiting factors involve limited resources, inconsistent institutional support, and generational differences in artistic preferences. The study concludes that art plays a key role in contemporary da’wah by enhancing religious engagement and aligning Islamic teachings with local culture, thereby providing guidance for educators, institutions, and policymakers in integrating arts into community programs, while also highlighting the need for future research employing longitudinal and multi-site designs to further understand art-driven religious transformation.